OC-087 Can faecal calprotectin reduce the demand for colonoscopy in patients with irritable bowel syndrome?. (23rd September 2015) - Whitehead, S J; Lee, L; Fang, Z; Sisson, G; Hutton, J; Logan, R P H
Abstract : Introduction: The diagnosis of irritable bowel syndrome (IBS) in primary care relies on typical clinical features, absence of alarm symptoms and normal tests. Apart from usual blood tests, patients are often referred to secondary care and often undergo GI imaging (Barium studies or endoscopy), despite NICE guidelines recommendation to the contrary. Faecal calprotectin (FC) appears to be a very sensitive test for activated neutrophils from the small and large bowel and so may allow the diagnosis of IBS to be established in primary care. Methods: 1. Outcomes based analysis of patients having a FC test between Jan 05-Jan 09 using HES, PACS and SNOMED CT pathology data sets. 2. Statistical analysis using Bayesian MCMC modelling of patient population data to determine cut-offs for computer modelling. 3. Linear modelling of two diagnostic strategies for costs and outcomes using a decision tree approach for a cohort of 1000 suspected IBS patients until diagnosis confirmed. Costs were limited to direct healthcare costs (ie, tests, endoscopies, drugs and outpatient visits). Outcomes were analysed for the number of correctly diagnosed IBS and IBD patients. Data inputs were drawn from published studies, established national databases, and expert clinical opinion. Results: From a data set of >16 000, 2419 patients aged <45 years (63% women) attending for the first time, were identified. PACS, ePR and patholology data bases identified pathology in 58% patients with FC >50. For the 1750 patients with negative results, computer modelling indicated that cut-offs <125 would represent 95% of normal population. For cost-effectiveness, modelling showed that cost-savings varied with sensitivity and specificity (see Abstract 087 ). In the base case, in comparison with ESR plus CRP, FC resulted in an additional 63 correctly diagnosed IBS patients and an additional 55 correctly diagnosed IBD patients at the initial test. Total costs were £312 143 for the FC cohort compared to £325 606 for the ESR plus CRP cohort, making the FC diagnostic strategy cost-saving. Sensitivity analysis identified the specificity and sensitivity of the tests as being key drivers of the results, in addition to the cost of colonoscopy and FC ELISA. Conclusion: These studies show that faecal calprotectin is more effective, in terms of diagnostic accuracy, and is a less costly diagnostic strategy for distinguishing IBS from IBD than the use of ESR plus CRP. Faecal calprotectin has the potential to improve the management of IBS patients in primary care by increasing the confidence with which diagnoses are made by healthcare professionals, and reducing the need for referral to secondary care.